â€œANIMAL DE SANGUE FRIOâ€ VS â€œHOMEOTERMOâ€: VELHA DÃšVIDA BIO-NOMENCLATURAL - Amaral, AfrÃ¢nio do (REVISTA DE AGRICULTURA, 2016)
â€œANIMAL DE SANGUE FRIOâ€ VS â€œHOMEOTERMOâ€: VELHA DÃšVIDA BIO-NOMENCLATURAL